Continuous‐Flow Synthesis of Adipic Acid from Cyclohexene Using Hydrogen Peroxide in High‐Temperature Explosive Regimes. Issue 6 (16th April 2013) - Damm, Markus; Gutmann, Bernhard; Kappe, C. Oliver
<x xml:space="preserve">Abstract</x> Safe only in a microreactor! The synthesis of adipic acid from cyclohexene by tungstic acid‐catalyzed oxidation using hydrogen peroxide following the classical Noyori protocol can be accomplished in good yields with residence times as short as 20 min at 140 °C using a safe and scalable microreactor environment. Under these intensified conditions the use of a phase‐transfer catalyst is not required.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>